Employability in the public sector: The impact of individual and organizational determinants - Vermeeren, Brenda; Van der Heijden, Beatrice (Frontiers in Psychology, 2022)
The importance of employability within organizations is increasing, due to various developments that initiate organizational changes. This study focuses on the employability in the public sector. While there seems to be a clear need for an employable public sector workforce, up until now there is little empirical research into the employability of workers in this sector, and into which specific individual and organizational characteristics influence it. Our outcomes show that public sector employees consider themselves to be reasonably employable internally, and that they rate their external employability slightly higher. Moreover, it was found that both individual (personality and risk-taking behavior) and organizational characteristics (transformational leadership and red tape) influence their employability. These results underline the dual responsibility of the employee and the organization in influencing workers’ employability within the public sector.